ANALISIS SEMIOTIKA PADA FILM “22 MENIT” KARYA HUSEEIN M. ATMOJO DAN GUNAWAN RAHARJA - Wiranti, Desy; Sunarsih, Eti; Wirawan, Gunta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the signs contained in the film 22 Minutes by Huseein M. Atmojo and Gunawan Raharja. This research also aims to describe the denotation meaning, connotation meaning, mythical meaning as well as the plan to implement the research results in literature learning in Secondary Schools. The method used in this research is qualitative method with descriptive form. The approach used in this research is a semiotic approach. The data source of this research is the movie 22 Minutes by Huseein M. Atmojo and Gunawan Raharja. The data collection technique in this research uses documentary study techniques. This research is analyzed using the theory of Roland Barthes and associated with the semiotic approach, which focuses on scenes related to denotation meaning, connotation meaning and mythical meaning. After analyzing, there are 37 data containing denotation meaning, connotation meaning and mythical meaning, the data obtained are 13 data of denotation meaning, 17 data of connotation meaning, and 7 data of myth. The results of this study are planned to be implemented in the making of teaching modules for the independent curriculum in class XI of Senior High School (SMA), namely on drama material in Chapter 5: Getting to Know Indonesia's Diversity Through Drama Performances. with Learning Objectives: 11.7 Learners summarize the feelings and characteristics of the characters and other instrinsic elements such as the setting of the story, events in the drama performance.